A Retrospective Study of Respiratory Viruses in a Four-Year Study of Nasal Swabs from Patients with Severe Influenza-like Symptoms in the Lazio Region, Italy - Giuseppe Sberna; Licia Bordi; Cosmina Mija; Enrico Girardi; Fabrizio Maggi; Eleonora Lalle (Viruses)
The global outbreak of severe acute respiratory syndrome-related coronavirus 2 (SARS-CoV-2) and the strategies adopted by different nations have affected and altered the transmission of different respiratory pathogens around the world. We examined the impact of SARS-CoV-2 on the spread of respiratory viruses in the period between 2021 and 2024 in patients with severe influenza-like symptoms in the Lazio region using multiplex PCR tests for the identification of common seasonal respiratory viruses. Our data reveal a change in the transmission of respiratory viruses from 2021 to 2024, with a sharp decline in the transmission of SARS-CoV-2 and a rise in the transmission of other respiratory viruses, especially influenza viruses, and human rhinovirus/enterovirus in 2024. Moreover, viral co-infections, both those involving two viruses and those involving three viruses, have also increased. This work shows how the spread of SARS-CoV-2 influenced the spread of other respiratory viruses over four years in patients with severe influenza-like symptoms in the Lazio region. In conclusion, the resurgence and fluctuation of various respiratory viruses emphasize the dynamic nature of viral epidemiology in the post-pandemic context and highlight the ongoing need for vigilant public health monitoring and intervention strategies.